Social and economic conditions and inequalities in the circumpolar Arctic. - Duhaime, Gérard; Everett, Karen; Lévesque, Sébastien; Taoyuan Wei; Baribeau, Marileine; Caron, Andrée (Statistics Norway, 2024)
This chapter updates and extends the previous comparative study of socio-economic and social conditions across the circumpolar Arctic, by comparing the situation in 2018 and 2012. Comparing the indicators over time allows us to verify whether the socio-economic models of the three geographical groups are still relevant. The socio-economic models are shaped by different factors, including political structures, emphasis on different economic industries, and transportation systems. The updated results continue to indicate that differences between the three geographical groups are shrinking, although there are increasing internal inequalities in some regions.